Barbie it takes two. Series 1, Best friends forever [videorecording (DVD)] (NCircle Entertainment, 2023)
Join Barbie "Malibu" Roberts and Barbie "Brooklyn" Roberts for fun, laughter and exciting new adventures. Follow Barbie and Barbie as they attend a year of performing arts high school in NYC.